2022
DOI: 10.1029/2021jb023597
|View full text |Cite
|
Sign up to set email alerts
|

Copper Isotopic Fractionation During Seafloor Alteration: Insights From Altered Basalts in the Mariana and Yap Trenches

Abstract: To further investigate copper (Cu) isotopic fractionation during seawater‐oceanic crust interactions, 13 subsamples across a basalt altering section and 12 bulk‐rock basalts from the southern Mariana and Yap trenches, western Pacific Ocean, were studied. We find that the δ65Cu values of the basalt section roughly increase from mid‐ocean ridge basalt‐like values (0.04% – 0.10%) in the core to higher values (up to 0.20%) near the core‐rim interface, and then lower values (down to −0.17%) at the rims. Isotopicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Guo et al. (2022) also proposed that the elevated δ 65 Cu values of the altered basalts from the Mariana and Yap trenches were due to the preferential adsorption of heavy Cu isotopes onto secondary minerals in the altered basalts (Busigny et al., 2018; Liu et al., 2019). Nevertheless, backscattered electron images of the studied lavas indicate that they do not contain secondary minerals (Figure S4 in Supporting Information S1).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Guo et al. (2022) also proposed that the elevated δ 65 Cu values of the altered basalts from the Mariana and Yap trenches were due to the preferential adsorption of heavy Cu isotopes onto secondary minerals in the altered basalts (Busigny et al., 2018; Liu et al., 2019). Nevertheless, backscattered electron images of the studied lavas indicate that they do not contain secondary minerals (Figure S4 in Supporting Information S1).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Guo et al. (2022) suggested that the elevated δ 65 Cu values in an altered basalt section from the southern Mariana trench were due to concentration‐driven diffusion induced by the dissolution of sulfide in the altered rims during alteration. However, our whole‐rock samples were collected from the core sections of each fresh sample (Figure S3 in Supporting Information S1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations